Cell survival, DNA damage, and oncogenic transformation after a transient and reversible apoptotic response - Tang, Ho Lam (The American Society for Cell Biology, 2012)
Apoptosis serves as a protective mechanism by eliminating damaged cells through programmed cell death. After apoptotic cells pass critical checkpoints, including mitochondrial fragmentation, executioner caspase activation, and DNA damage, it is assumed that cell death inevitably follows. However, this assumption has not been tested directly. Here we report an unexpected reversal of late-stage apoptosis in primary liver and heart cells, macrophages, NIH 3T3 fibroblasts, cervical cancer HeLa cells, and brain cells. After exposure to an inducer of apoptosis, cells exhibited multiple morphological and biochemical hallmarks of late-stage apoptosis, including mitochondrial fragmentation, caspase-3 activation, and DNA damage. Surprisingly, the vast majority of dying cells arrested the apoptotic process and recovered when the inducer was washed away. Of importance, some cells acquired permanent genetic changes and underwent oncogenic transformation at a higher frequency than controls. Global gene expression analysis identified a molecular signature of the reversal process. We propose that reversal of apoptosis is an unanticipated mechanism to rescue cells from crisis and propose to name this mechanism “anastasis” (Greek for “rising to life”). Whereas carcinogenesis represents a harmful side effect, potential benefits of anastasis could include preservation of cells that are difficult to replace and stress-induced genetic diversity.